Relationship between Civil Service Ethics and Civil Service Law: Some Theoretical Issues - Pham Hong, Thai; Pham Thi, Giang (VNU Journal of Science: Legal Studies; Vol 34 No 3, 2018)
Civil service ethics and civil service law are the phenomena and the components of the civil service culture, which are closely related and interact with one another to form a unified system for regulating civil service behaviours of civil officials and employees. The article discusses the ethics of civil service and the relationship between civil service ethics and civilservice law by analysing the unity, disunity, difference and the interaction of these phenomena. Keywords: Civil service ethics, relationship, civilservice law.